PERSEPSI DONATUR MENGENAI INFORMASI AKUNTANSI ORGANISASI PENGELOLAAN ZAKAT - Rintasari, Nugraheni (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
This research purpose to know Donorâs perception concern accounting information in zakah management organization. The aim of this research based on three survey results. First, survey by Islamic State University Syarif Hidayatullah at 2007 resulted that 75% people unwilling donate in zakah institution who they didnât know its accountability. Second, survey by PIRAC (Public Interest Research and Advocacy Center) at 2007 resulted that 47% people rejected to donate in zakah institution because their incredulity to institution. Third, survey by PIRAC (Public Interest Research and Advocacy Center) other at 2007 resulted 70% people disposed to public fund power pattern report by institution. Accounting information in this research based on Exposure Draft Financial Accounting Standards 109 concerning Zakah, Infak, Sedekah Accounting and Zakah Management Organization Accounting Guide by Zakah Forum. This research use survey method by quissioner. Respondent of this research are Donor who donate zakah, infak, sedekah to zakah institution in Yogyakarta. This research entangles 138 respondent. Validity test for quisioner by Pearson Product Moment Methode and reliability test by Croanbach Alpha tehnique. Hypothesis testing by t-test one sample.The result shows that Donors donât need accounting information by financial statement over all but only some items in financial statement. They are cash, zakah balance, infaq balance, zakah fund, zakah give to other institution, zakah give to mustahiq, zakah fund institution, zakah give to mustahiq specifically, cash by zakah fund, zakah for office operational, and program of zakah institution.